Lesions of the triangular fibrocartilage and extensor carpi ulnaris tendon in tennis: biomechanics and clinical diagnosis - Verstreken, F. (Medicine and Science in Tennis, 2007)
The wrist joint has a unique range of motion pattern with three degrees of freedom: flexion-extension, ulnar-radial deviation and rotation around its axis: pronation and supination. The ulnar column is the stable part of the wrist, around which the radius and hand rotate with different wrist movements. A complex anatomical organisation is necessary to allow this motion pattern. The triangular fibrocartilaginous complex (TFCC) plays a key role, as it stabilises the distal radio-ulnar joint and the ulnar carpus, but also allows better load transfer over the ulnar side of the wrist. The load along the ulna, relative to the radius increases with positive ulnar variance and with ulnar deviation of the wrist. A recent in vitro and in vivo study has shown higher loading of the ulnar part of the wrist then previously thought, reaching up to 64% of total force transmission over the wrist joint.